Circular economy: A new direction for the sustainability of the hotel industry in Romania? - Rodica Pamfilie; Daniela Firoiu; Adina-Gabriela Croitoru; George Horia Ioan Ionescu (Amfiteatru Economic Journal, 2018)
The present article deals with aspects related to the transition to a new model of economy - the circular economy - a more appropriate model for the current tendencies of ensuring the sustainability of economic processes. Tourism, as an economic branch with strong dynamics in recent years, is one of the areas where resource conservation and environmental protection are of significant importance. Circular tourism, derived from the principles of circular economy, aims at recycling tourism resources and favoring the sustainable development of the environment, thus giving tourists a greater sense of responsibility. The authors sought to study the influence of the implementation of integrated quality-environment-security systems on the economic performance of hotel establishments in Romania from the perspective of industry managers, as a starting point for determining the applicability of the principles of circular economy in this sector. In order to study this influence, questionnaires were addressed to tourism operators in order to establish the existing link between the implementation of ISO 9001, ISO 14001 and OHSAS 18001 standards and the economic, social and environmental performance of those operators. From the perspective of the systemic approach and analyzing the obtained data, the authors of the paper argue that the hotel industry in Romania is not yet sufficiently prepared to adopt the principles of the circular economy, the adoption of an integrated management system not having as much influence as believed on the performances of the operators in the field.
Keywords: L83; Q01; Q56; Z32; 330; sustainable development; circular economy; circular tourism; integrated management system; economical performance